High-water-absorption sponge and preparation method and application thereof
By using a highly absorbent sponge with composite polyether polyol, oat polypeptide and water-absorbing resin in polyurethane cotton, the problem of easy deformation and insufficient rebound performance after liquid absorption is solved, and the good water absorption, flexibility and rebound of the sponge is achieved, which is suitable for the preparation of cotton cotton.
Patent Information
- Application Number
- CN202411967157.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing polyurethane cotton pads are prone to deform after absorbing liquid, and cannot meet the needs when high rebound performance is required, which has certain limitations.
A highly absorbent sponge composed of composite polyether polyol, oat polypeptide and water-absorbing resin is used to improve the water absorption, flexibility and resilience of the sponge through specific ratios and processes.
It achieves good water absorption, flexibility and resilience of the sponge, avoids deformation problems, and provides high resilience performance when needed, and is suitable for the preparation of cosmetic cotton.
Smart Images

Figure BDA0005218624410000071 
Figure BDA0005218624410000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane sponges, and in particular to a highly water-absorbent sponge and a preparation method and application thereof. Background Art
[0002] As the spending power of the global female consumer group continues to increase, the cosmetics industry is booming at an unprecedented rate. As an indispensable auxiliary tool in daily skin care, the demand for cosmetic cotton is also expanding. Nitrile rubber cosmetic cotton may cause uneven penetration of cosmetic liquid due to its large pore size, with some areas being too wet and some areas being dry, affecting the skin care effect. At the same time, nitrile rubber is relatively hard and lacks sufficient softness, which may cause a certain sense of pressure or discomfort to the skin when used. In addition, although its rebound performance is strong, excessive rebound sometimes leads to insufficient fit between the cosmetic cotton and the skin, affecting the absorption of cosmetic liquid.
[0003] In this context, polyurethane cosmetic cotton pads have gradually emerged with their unique advantages. Compared with traditional nitrile rubber cosmetic cotton pads, polyurethane cosmetic cotton pads have smaller pores, which can more accurately control the penetration of cosmetic liquid and avoid waste; the smaller depth design makes the cosmetic cotton pads fit the facial contour better and more convenient to use; the flatter surface reduces the discomfort when rubbing against the skin and improves the user experience; the better hydrophilicity ensures that the cosmetic liquid can be quickly and evenly absorbed and released to the skin.
[0004] However, the common polyurethane cosmetic cotton on the market, although it has overcome some shortcomings of nitrile rubber cosmetic cotton to a certain extent, is not perfect. Although polyurethane materials have good hydrophilicity, some products may have the problem of easy deformation after absorbing liquid, which affects the subsequent use effect. At the same time, although its mechanical properties are improved compared to nitrile rubber, in some occasions where higher rebound performance is required, polyurethane cosmetic cotton may still not meet the needs, showing certain limitations. Therefore, in the continuous development of the cosmetics industry, the research and development and innovation of cosmetic cotton materials still have a long way to go. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a highly absorbent sponge having the advantages of good water absorption, high resilience, and not easy to deform, as well as a preparation method and application thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] In a first aspect, the present invention provides a highly absorbent sponge, which is composed of a component A and a component B in a mass ratio of 100:(60-70); wherein the component A and the component B are respectively composed of the following raw materials in parts by weight:
[0008] Component A: 30-50 parts of foaming agent, 2-5 parts of chain extender, 3-5 parts of cell opener, 1-2 parts of color paste;
[0009] Component B: 25-70 parts of composite polyether polyol, 10-30 parts of toluene diisocyanate, 0.5-1.5 parts of silicone oil, 0.2-1 parts of catalyst, 5-15 parts of oat polypeptide and 1-5 parts of water-absorbing resin;
[0010] Among them, the composite polyether polyol is a composition of poly(ethylene oxide-propylene oxide) triol, polyoxypropylene triol and sorbitol polyether polyol in a mass ratio of 1:(0.5-1):(1.1-1.5); the manufacturer of poly(ethylene oxide-propylene oxide) triol is CNOOC Shell Petrochemical Co., Ltd., the model is SC56-16S, and the number average molecular weight is 3000; the manufacturer of polyoxypropylene triol is Shandong Bluestar Dongda Co., Ltd., the model is MN-700, the number average molecular weight is 700, and the functionality is 3; the manufacturer of sorbitol polyether polyol is Haierma, the model is HM-635A, and the number average molecular weight is 600.
[0011] The composite polyether polyol of the present invention is composited by a high molecular weight polyether polyol and a low molecular weight polyether polyol, wherein the high molecular weight polyether polyol is poly(oxyethylene-oxypropylene) triol, and the low molecular weight polyether polyol is polyoxypropylene triol and sorbitol polyether polyol, wherein the sorbitol polyether polyol has the unique advantage of high EO (ethylene oxide) content, and can significantly improve the hydrophilicity of the sponge, so that the sponge can quickly absorb and diffuse when in contact with water, and at the same time, it also gives the sponge more excellent softness, making the sponge feel more comfortable; the addition of polyoxypropylene triol forms a good complement to the sorbitol polyether polyol, which not only enhances the structural stability of the sponge, but also through its unique chemical properties, The synergistic effect with high molecular weight poly (ethylene oxide - propylene oxide) triol makes the sponge have a certain resilience while maintaining excellent hydrophilicity and softness. This resilience enables the sponge to better restore to its original shape during use and prolongs its service life. High molecular weight poly (ethylene oxide - propylene oxide) triol is another important component in the composite system. Its macromolecular chain structure provides good support and stability for the sponge, so that the sponge can maintain its shape and is not easily deformed when subjected to external forces. At the same time, it is intertwined with low molecular weight poly (propylene oxide) triol and sorbitan polyether polyol to form a tight and orderly network structure. The three work synergistically to give the polyurethane sponge excellent hydrophilicity, flexibility and resilience.
[0012] Oat polypeptide is a biological macromolecule containing active groups such as amino and carboxyl groups. Since oat polypeptide has excellent water solubility, these water-soluble components can be evenly dispersed in the resin matrix during the solidification and molding process of polyurethane resin. This evenly dispersed state enables the sponge to form a large number of fine and uniform pore structures during solidification. These dense pores not only increase the porosity of the sponge, but also greatly improve the water absorption, flexibility and resilience of the sponge, so that the sponge can quickly absorb and keep moist when it comes into contact with water, giving people a more comfortable use experience.
[0013] Preferably, the blowing agent is water.
[0014] Preferably, the chain extender is a liquid secondary diamine chain extender.
[0015] Preferably, the catalyst is a composition of an amine catalyst and an organotin catalyst in a mass ratio of 1:(0.5-1). More preferably, the amine catalyst is triethylenediamine and the organotin catalyst is dibutyltin dilaurate.
[0016] Preferably, the mass ratio of poly(oxyethylene-oxypropylene) triol, polyoxypropylene triol and sorbitan polyether polyol is 1:0.8:1.2.
[0017] Preferably, the manufacturer of the water-absorbent resin is Evonik Industries, Ltd., and the model number is -Pac 300.
[0018] Preferably, the manufacturer of the silicone oil is Evonik Degussa, and the model is B8002.
[0019] Preferably, the manufacturer of the cell opener is Jiangsu Bader Polyurethane Co., Ltd., and the model is MK01.
[0020] In a second aspect, the present invention provides a method for preparing the highly absorbent sponge according to the first aspect, comprising the following steps:
[0021] S1. Stir and mix the foaming agent, chain extender, cell opening agent and color paste in the formulated amount to obtain component A product;
[0022] S2. Add composite polyether polyol, silicone oil, catalyst and water-absorbent resin to the component A product obtained in step S1, heat to 100-110° C. and perform vacuum dehydration for 1.5-2 hours, then cool to 30-40° C., add the formulated amount of toluene diisocyanate and oat polypeptide, heat to 70-75° C. and keep the reaction for 2-2.5 hours, cool and discharge to obtain the highly absorbent sponge.
[0023] Preferably, in step S1, the stirring speed is 50-80 r / min, and the stirring time is 20-40 min.
[0024] Preferably, the mass percentage of isocyanate in the highly absorbent sponge is 7.5-8.5%.
[0025] In a third aspect, the present invention provides use of the highly absorbent sponge described in the first aspect in preparing cosmetic cotton.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The highly water-absorbent sponge of the present invention is added with a composite polyether polyol, which is composed of a high molecular weight polyether polyol (i.e., poly(ethylene oxide-propylene oxide) triol) and a low molecular weight polyether polyol (i.e., polyoxypropylene triol, sorbitol polyether polyol), wherein sorbitol polyether polyol improves the hydrophilicity and softness of the sponge, and polyoxypropylene triol enhances the structural stability, and the two and the high molecular weight polyether polyol synergistically give the sponge resilience. In addition, oat polypeptides with good water solubility are also added to the highly water-absorbent sponge of the present invention, which can further improve the water absorption, flexibility and resilience of the sponge. Therefore, the sponge provided by the present invention has good water absorption, flexibility and resilience, and is suitable for preparing cosmetic cotton. DETAILED DESCRIPTION
[0028] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0029] The sources of raw materials used in the following examples and comparative examples are as follows:
[0030] Chain extender: 4,4'-bis-sec-butylaminodiphenylmethane, manufactured by American DorfKetal Chemical Company, model 4200;
[0031] Cell opener: The manufacturer is Jiangsu Bader Polyurethane Co., Ltd., model MK01;
[0032] Poly(ethylene oxide-propylene oxide) triol: manufacturer is CNOOC Shell Petrochemical Co., Ltd., model is SC56-16S, number average molecular weight is 3000;
[0033] Polyoxypropylene triol: manufacturer is Shandong Bluestar Dongda Co., Ltd., model number is MN-700, number average molecular weight is 700, functionality is 3;
[0034] Sorbitol polyether polyol: manufacturer is Haierma, model is HM-635A, number average molecular weight is 600;
[0035] Toluene diisocyanate: manufacturer is Covestro AG, model number is T80;
[0036] Silicone oil: polysiloxane-polyalkylene oxide block copolymer, manufacturer: Evonik Degussa, model: B8002;
[0037] Amine catalyst: triethylenediamine, manufactured by Evonik Industries, Germany, model DABCO33LV;
[0038] Organic tin catalyst: dibutyltin dilaurate, manufactured by American Momentive Advanced Materials Company, model D22
[0039] Oat peptide: manufacturer is Changzhou Yangsen Biotechnology Co., Ltd., model number is JR-YM02;
[0040] Soybean peptide: manufacturer is Rushan Hualong Biotechnology Co., Ltd., model number is FPD500;
[0041] Water-absorbent resin: manufacturer is Evonik Industries, model number is -Pac 300;
[0042] Color paste: The pigment is purple, the manufacturer is Dongguan Guangsiyuan Polyurethane Materials Co., Ltd., and the model is SK107.
[0043] Unless otherwise specified, other materials, reagents, etc. used in the examples and comparative examples can be obtained from commercial sources.
[0044] Example 1
[0045] A highly absorbent sponge is composed of a component A and a component B in a mass ratio of 100:65; wherein the component A and the component B are respectively composed of the following raw materials in parts by weight:
[0046] Component A: 40 parts of foaming agent, 4 parts of chain extender, 4 parts of cell opener, 3 parts of color paste;
[0047] Component B: 60 parts of composite polyether polyol, 20 parts of toluene diisocyanate, 1 part of silicone oil, 0.5 parts of catalyst, 10 parts of oat polypeptide and 3 parts of water-absorbing resin;
[0048] The composite polyether polyol is a composition of poly(ethylene oxide-propylene oxide) triol, polyoxypropylene triol and sorbitol polyether polyol in a mass ratio of 1:0.8:1.2, the foaming agent is water, and the catalyst is a composition of an amine catalyst and an organotin catalyst in a mass ratio of 1:0.6;
[0049] The method for preparing the highly absorbent sponge comprises the following steps:
[0050] S1. Stir and mix the foaming agent, chain extender, cell opener and color paste in the formulated amount at a speed of 70 r / min for 30 min to obtain a component A product;
[0051] S2. Add composite polyether polyol, silicone oil, catalyst and water-absorbent resin to the component A product obtained in step S1, heat to 105° C. and perform vacuum dehydration for 2 hours, then cool to 35° C., add the formulated amount of toluene diisocyanate and oat polypeptide, heat to 75° C. and keep the reaction for 2 hours until the mass percentage of isocyanate is 8.0%, cool and discharge to obtain the highly absorbent sponge.
[0052] Example 2
[0053] A highly absorbent sponge is composed of a component A and a component B in a mass ratio of 100:60; wherein the component A and the component B are respectively composed of the following raw materials in parts by weight:
[0054] Component A: 30 parts of foaming agent, 2 parts of chain extender, 3 parts of cell opener, 1 part of color paste;
[0055] Component B: 25 parts of composite polyether polyol, 10 parts of toluene diisocyanate, 0.5 parts of silicone oil, 0.2 parts of catalyst, 5 parts of oat polypeptide and 1 part of water-absorbing resin;
[0056] Wherein, the composite polyether polyol is a composition of poly(ethylene oxide-propylene oxide) triol, polyoxypropylene triol and sorbitol polyether polyol in a mass ratio of 1:0.5:1.1, the foaming agent is water, and the catalyst is a composition of an amine catalyst and an organotin catalyst in a mass ratio of 1:0.5;
[0057] The method for preparing the highly absorbent sponge comprises the following steps:
[0058] S1. Stir and mix the foaming agent, chain extender, cell opener and color paste in the formula at a speed of 50 r / min for 40 min to obtain component A product;
[0059] S2. Add composite polyether polyol, silicone oil, catalyst and water-absorbent resin to the component A product obtained in step S1, heat to 100° C. and dehydrate under vacuum for 1.5 hours, then cool to 30° C., add the formulated amount of toluene diisocyanate and oat polypeptide, heat to 70° C. and keep warm for 2 hours to react until the mass percentage of isocyanate is 7.5%, cool and discharge to obtain the highly absorbent sponge.
[0060] Example 3
[0061] A highly absorbent sponge is composed of a component A and a component B in a mass ratio of 100:70; wherein the component A and the component B are respectively composed of the following raw materials in parts by weight:
[0062] Component A: 50 parts of foaming agent, 5 parts of chain extender, 5 parts of cell opener, 2 parts of color paste;
[0063] Component B: 70 parts of composite polyether polyol, 30 parts of toluene diisocyanate, 1.5 parts of silicone oil, 1 part of catalyst, 15 parts of oat polypeptide and 5 parts of water-absorbing resin;
[0064] Wherein, the composite polyether polyol is a composition of poly(ethylene oxide-propylene oxide) triol, polyoxypropylene triol and sorbitol polyether polyol in a mass ratio of 1:1:1.5, the foaming agent is water, and the catalyst is a composition of an amine catalyst and an organotin catalyst in a mass ratio of 1:1;
[0065] The method for preparing the highly absorbent sponge comprises the following steps:
[0066] S1. Stir and mix the foaming agent, chain extender, cell opener and color paste in the formula at a speed of 80 r / min for 20 min to obtain component A product;
[0067] S2. Add composite polyether polyol, silicone oil, catalyst and water-absorbent resin to the component A product obtained in step S1, heat to 110° C. and perform vacuum dehydration for 2 hours, then cool to 40° C., add the formulated amount of toluene diisocyanate and oat polypeptide, heat to 75° C. and keep the reaction for 2.5 hours until the mass percentage of isocyanate is 8.5%, cool and discharge to obtain the highly absorbent sponge.
[0068] Comparative Example 1
[0069] The difference between Comparative Example 1 and Example 1 is that the total mass of the added composite polyether polyol remains unchanged, no poly(ethylene oxide-propylene oxide) triol is added, and polyoxypropylene triol and sorbitol polyether polyol with a mass ratio of 0.8:1.2 are used to make up for the missing amount.
[0070] Comparative Example 2
[0071] The difference between Comparative Example 2 and Example 1 is that the total mass of the added composite polyether polyol remains unchanged, polyoxypropylene triol is not added, and poly(oxyethylene-oxypropylene) triol and sorbitol polyether polyol in a mass ratio of 1:1.2 are used to make up for the missing amount.
[0072] Comparative Example 3
[0073] The difference between Comparative Example 3 and Example 1 is that the total mass of the added composite polyether polyol remains unchanged, sorbitol polyether polyol is not added, and poly(ethylene oxide-propylene oxide) triol and polypropylene oxide triol in a mass ratio of 1:0.8 are used to make up for the missing amount.
[0074] Comparative Example 4
[0075] The difference between Comparative Example 4 and Example 1 is that no oat polypeptide is added.
[0076] Comparative Example 5
[0077] The difference between Comparative Example 5 and Example 1 is that an equal amount of soybean polypeptide is used to replace oat polypeptide.
[0078] Comparative Example 6
[0079] The difference between Comparative Example 6 and Example 1 is that the total mass of the added composite polyether polyol remains unchanged, and the mass ratio of poly(ethylene oxide-propylene oxide) triol, polyoxypropylene triol and sorbitol polyether polyol is 0.8:1:1.2.
[0080] Comparative Example 7
[0081] The difference between Comparative Example 7 and Example 1 is that the total mass of the added composite polyether polyol remains unchanged, and the mass ratio of poly(ethylene oxide-propylene oxide) triol, polyoxypropylene triol and sorbitol polyether polyol is 1:1.2:0.8.
[0082] Comparative Example 8
[0083] The difference between Comparative Example 8 and Example 1 is that the total mass of the added composite polyether polyol remains unchanged, and the mass ratio of poly(ethylene oxide-propylene oxide) triol, polyoxypropylene triol and sorbitol polyether polyol is 1.2:0.8:1.
[0084] Performance Testing
[0085] The sponges prepared in Examples 1-3 and Comparative Examples 1-8 were subjected to performance tests, wherein the elongation at break was tested according to GB / T6344-1996 standard; the test method for rebound in water was as follows: the cosmetic cotton product was put into water, taken out after 10 minutes, and the water was squeezed out forcefully, and the time required for the product to recover to its original state was measured; the test method for water absorption rate was as follows: a dry sponge with a mass of m1 was immersed in distilled water at 23±2°C for 24 hours, and then quickly taken out after soaking, the excess water was dripped off, and it was naturally dried in the air for 15 minutes, and then the mass at this time was recorded as m2, and the water absorption rate was calculated according to the formula W=(m2-m1) / V×100%, where V is the volume cm 3 , specific data are shown in Table 1.
[0086] Table 1 Performance test results of polyurethane sponge in each group
[0087]
[0088]
[0089] Note: The higher the elongation at break, the better the flexibility of the sponge; the shorter the rebound time in water, the faster the rebound of the sponge; the greater the water absorption rate, the stronger the hydrophilicity and water absorption of the sponge.
[0090] The data in Table 1 show that the sponges of Examples 1-3 all have higher elongation at break, shorter rebound time in water, and higher water absorption rate. It can be seen that the sponges of Examples 1-3 all have good hydrophilicity, good resilience and flexibility, among which the sponge of Example 1 has the best effect.
[0091] By comparing the data of Example 1 and Comparative Examples 1-3 in Table 1, it can be seen that the sponge of Example 1 has a higher elongation at break, a shorter rebound time, and a greater water absorption rate, indicating that the combination of poly(ethylene oxide-propylene oxide) triol, polyoxypropylene triol and sorbitan polyether polyol in a specific dosage ratio is more conducive to forming a sponge with good water absorption, high rebound and strong flexibility.
[0092] Comparing the data of Example 1 and Comparative Example 4 in Table 1, it can be seen that the water absorption, flexibility and resilience of Comparative Example 4 are all lower than those of Example 1. This may be because the oat polypeptide has excellent water solubility. During the coagulation and molding process of the polyurethane resin, the oat polypeptide can be evenly dispersed in the resin matrix, so that the sponge can form a large number of fine and uniform pore structures during coagulation, which not only increases the porosity of the sponge, but also greatly improves the water absorption, flexibility and resilience of the sponge.
[0093] By comparing the data of Example 1 and Comparative Example 5 in Table 1, it can be seen that the addition of oat polypeptide can obtain better performance than the addition of soybean polypeptide. This may be because the oat polypeptide itself has strong water absorption. Therefore, the sponge with the addition of oat polypeptide can obtain better performance than the sponge with the addition of soybean polypeptide.
[0094] By comparing the data of Example 1 with Comparative Examples 6-8 in Table 1, it can be seen that when the mass ratio of poly(ethylene oxide-propylene oxide) triol, polypropylene oxide triol and sorbitan polyether polyol is 1:(0.5-1):(1.1-1.5), the water absorption, flexibility and resilience of the sponge all reach a better level.
[0095] In summary, the polyurethane sponge of the present invention obtains good hydrophilicity, fine pores, and good resilience by adding composite polyether polyol and oat polypeptide in a specific mass ratio, and is suitable for preparing cosmetic cotton.
[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A highly absorbent sponge, characterized in that: The composition is composed of component A and component B in a mass ratio of 100:(60-70); wherein component A and component B are respectively composed of the following raw materials in parts by weight: Component A: 30-50 parts of foaming agent, 2-5 parts of chain extender, 3-5 parts of cell opener, 1-2 parts of color paste; Component B: 25-70 parts of composite polyether polyol, 10-30 parts of toluene diisocyanate, 0.5-1.5 parts of silicone oil, 0.2-1 parts of catalyst, 5-15 parts of oat polypeptide and 1-5 parts of water-absorbing resin; Among them, the composite polyether polyol is a composition of poly(ethylene oxide-propylene oxide) triol, poly(propylene oxide triol) and sorbitol polyether polyol in a mass ratio of 1:(0.5-1):(1.1-1.5); the manufacturer of poly(ethylene oxide-propylene oxide) triol is CNOOC Shell Petrochemical Co., Ltd., the model is SC56-16S, and the number average molecular weight is 3000; the manufacturer of poly(propylene oxide triol) is Shandong Bluestar Dongda Co., Ltd., the model is MN-700, the number average molecular weight is 700, and the functionality is 3; the manufacturer of sorbitol polyether polyol is Haierma, the model is HM-635A, and the number average molecular weight is 600.
2. The highly absorbent sponge according to claim 1, characterized in that: The raw material is selected from at least one of (I)-(II): (I) the blowing agent is water; (II) The chain extender is a liquid secondary diamine.
3. The highly absorbent sponge according to claim 1, characterized in that: The catalyst is a composition of an amine catalyst and an organic tin catalyst in a mass ratio of 1:(0.5-1).
4. The highly absorbent sponge according to claim 1, characterized in that: The manufacturer of the water-absorbent resin is Evonik Industries, Inc., and the model number is -Pac 300.
5. The highly absorbent sponge according to claim 1, characterized in that: The manufacturer of the silicone oil is Evonik Degussa, and the model is B8002.
6. The highly absorbent sponge according to claim 1, characterized in that: The manufacturer of the cell opener is Jiangsu Bader Polyurethane Co., Ltd., and the model is MK01.
7. The method for preparing the highly absorbent sponge according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Stir and mix the foaming agent, chain extender, cell opening agent and color paste in the formulated amount to obtain component A product; S2. Add composite polyether polyol, silicone oil, catalyst and water-absorbent resin to the component A product obtained in step S1, heat to 100-110° C. and perform vacuum dehydration for 1.5-2 hours, then cool to 30-40° C., add the formulated amount of toluene diisocyanate and oat polypeptide, heat to 70-75° C. and keep the reaction for 2-2.5 hours, cool and discharge to obtain the highly absorbent sponge.
8. The method for preparing a highly absorbent sponge according to claim 7, characterized in that: In the step S1, the stirring speed is 50-80 r / min, and the stirring time is 20-40 min.
9. The method for preparing a highly absorbent sponge according to claim 7, characterized in that: The mass percentage of isocyanate in the highly absorbent sponge is 7.5-8.5%.
10. Use of the highly absorbent sponge according to any one of claims 1 to 6 in preparing cosmetic cotton.
Citation Information
Patent Citations
Preparation method of biodegradable nasal hemostatic sponge
CN104031287A
Degradable polyurethane foam and application thereof
CN107286313A